The holy fools: a theological enquiry - Thomas, Andrew (2009)
What is the significance of the deployment of madness in the early Christian ascetic experience of holiness? The first Byzantine holy fools – themselves critics of monastic orders – represent the consistent and logical conclusion of the theology and practice of the early Christian ascetics, and in particular that of the followers of Anthony and Pachomius. The flight to the desert of the first Christian anchorites and coenobites was an attempt to transform the experience and theology of holiness in church and society by transgressing the rules and thoughts of the city in a practical outworking of negative theology. The transgressive behaviour of the holy fools renewed that transformation by accepting neither secular nor religious truth and life. Where desert fathers and mothers had transformed the production of norms by their obedience and ascetic transcendence of human life, holy fools undermined the religious production of norms through their masterless obedience, defeat of vainglory, and foreignness to self. The transformation of the production of ethical knowledge amongst early Christian ascetics – through control of passions, representations, and silence – was followed through by the holy fools’ apophatic babble and rejection of religious loci of knowledge production in liturgy, confession, religious community and ecclesial authority. As a continuation of ascetic methods of reforming the self’s relation to society by brutal truthtelling and truth-hearing, the holy fools used self-ostracising insult and laughter to follow divine truth into the periphery without legislating universal modesty and submission to group truths. As such, the holy fools exemplify the practices most idealised in early Christian asceticism – humility, suspicion of fixed orders and truths, apophatic critique of doctrine and legislation – with renewed innovation and commitment to city life. They applied the strategic moves and principles of negative theology to the Christian theology and practice of holiness through aspiring to desert freedom, the practice of ignorance, and the unserious self.